Prototipagem como forma alternativa para realização de cranioplastia com metilmetacrilato: Nota técnica - Yacubian-Fernandes, Adriano [UNESP]; Laronga, Paulo Roberto; Coelho, Régis Antônio; Ducati, Luis Gustavo; Silva, Mateus Violin (FapUNIFESP (SciELO), 2004)
The prototyping is a method for reconstruction of human body segments by computer software. It has been used in neurosurgery for cranial reproduction in patients allowing the programming of surgical procedures and the production of prosthesis to reconstruct bone failures in the skull. We present two cases of cranioplasty performed with the use of acrylic prosthesis constructed by prototyping. After 10 months of follow-up, they donot present signs of infection and show good aesthetic result. The advantages pointed at the literature for this method (reduction of surgical time, easy technical handle, and good aesthetic result) were confirmed.
Prototyping as an alternative to cranioplasty using methylmethacrylate: Technical note
Keywords: Methylmethacrylate; Neurosurgery; Skull-plastic surgery; methacrylic acid methyl ester; adult; case report; computer program; cranioplasty; device; esthetics; female; human; infection risk; male; neurosurgery; outcomes research; plastic surgery; prosthesis failure; surgical technique; Aged; Computer-Aided Design; Craniotomy; Female; Follow-Up Studies; Humans; Male; Middle Aged; Models, Anatomic; Prostheses and Implants; Prosthesis Implantation; Skull; Treatment Outcome